A system approach to the self: Interpretive phenomenological analysis - Erdoğan, Ömer (Elsevier BV, 2024)
The study aims to determine the life experiences that affect the formation of permanent identity features that form the self during adolescence and to determine the importance of these identity features for adolescents. For this purpose, in-depth interviews were conducted with 8 participants, 4 of whom were women and 4 of whom were men, between the ages of 22-24, to understand the life experiences that affect their self-development during childhood and adolescence. Four of the participants are university students, and 4 of them are high school graduates. Interviews and analyses were carried out within the Interpretive phenomenological analysis principles framework. According to the results of the analysis obtained from the interviews, it was found that the most influential factor on self-development was family communication orientation in childhood, and the participants who grew up in families with a conversation orientation had more positive emotions during childhood, saw themselves as part of the family more, and established more successful friendships. On the other hand, participants from families with a conformity orientation had more negative feelings in childhood, had a lower sense of belonging to the family, and were found to be less successful in friendships.
Keywords: H1-99; Science (General); Family communication orientation; Self-development; Social sciences (General); Q1-390; Identity crisis; Identity characteristics; Research Article; 4. Education; 16. Peace & justice; 3. Good health